The Exfoliation of Graphene in Liquids by Electrochemical, Chemical, and Sonication‐Assisted Techniques: A Nanoscale Study. (17th April 2013) - Xia, Zhen Yuan; Pezzini, Sergio; Treossi, Emanuele; Giambastiani, Giuliano; Corticelli, Franco; Morandi, Vittorio; Zanelli, Alberto; Bellani, Vittorio; Palermo, Vincenzo
Abstract The different exfoliation routes of graphite to produce graphene by sonication in solvent, chemical oxidation and electrochemical oxidation are compared. The exfoliation process and roughening of a flat graphite substrate is directly visualized at the nanoscale by scanning probe and electron microscopy. The etching damage in graphite and the properties of the exfoliated sheets are compared by Raman spectroscopy and X‐ray diffraction analysis. The results show the trade‐off between exfoliation speed and preservation of graphene quality. A key step to achieve efficient exfoliation is to couple gas production and mechanical exfoliation on a macroscale with non‐covalent exfoliation and preservation of graphene properties on a molecular scale.